Evaluating Sex Differences in Efficacy, Safety and Pharmacokinetics in Patients Treated with Cannabis by a Metered-Dose Inhaler - Joshua Aviram; Marek Glezerman; Eytan Hayam; Rostislav Belobrov; Shiri Procaccia; David Meiri; Elon Eisenberg (Pharmaceuticals, 2023)
Background: Clinical studies on medical cannabis (MC) treatment have shown sex-related differences, including higher susceptibility to adverse events among women and greater analgesia among men. Here, we used the Syqe metered-dose inhaler (MDI) and a single chemovar to analyze sex differences. Methods: A total of 1249 Israeli chronic pain patients were assessed for pain intensity, sleep and adverse events (AEs) over 240 days. Results: Following the first two weeks, no significant sex differences were found in the effectiveness or safety of MC treatment (p > 0.05). Inhaled Δ9-THC doses did not vary significantly between sexes (p > 0.05) except in the first month of treatment. Pain reduction and sleep improvement were similar for both sexes (p > 0.05). The overall rate of AEs was equal and relatively low at 10% (n = 65, 10% of women and n = 60, 10% of men; χ2 (1) = 0.05, p = 0.820). A secondary analysis of pharmacokinetic data showed no significant differences between sexes in Δ9-THC and its metabolite pharmacokinetics, cardiovascular measures, or AE severity (p > 0.05). Conclusions: Uniform MC treatment via the Syqe MDI showed no sex differences in short-term effectiveness, safety and pharmacokinetics, nor in long-term effects, under “real-life” conditions. These findings provide insights into MC treatment which may inform clinical practice and policy-making in the field.